Sismantik: Empowerment of Larvae Monitoring Students in Reducing Cases of Dengue Hemorrhagic Fever (DHF) - Dewi Susanna; Kholis Ernawati; Umar Fahmi Ahmadi; Hermansyah Hasan; Ritawati Ritawati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Empowering the primary school students as larvae monitor that play a strategic role in reducing cases of dengue hemorrhagic fever (DHF) through the behavior of mosquito nests eradication (MNE/PSN) in their neighborhoods. The objective was to empower the primary school students as larvae monitor in the Kutaraja, Banda Aceh Municipality. The study conducted in July – October 2017. We conducted activities as follows: a) advocacy and socialization of activities to stakeholders in Kutaraja areas, (including primary health center and the schools), b) modules preparation, c) training of larva monitoring students), d) Focus Group Discussion (FGD) with stakeholder of the school for evaluation and the next community service programs, and e) periodic larvae inspection by students were trained. The results showed: a) there was significant knowledge between pre- and post-intervention (p = 0.004). The larva monitoring was performed 4 times every Sunday. The number of larvae free index (LFI/ABJ) higher in the fourth inspection than others.